PENGARUH PERSEPSI SISWA DAN SIKAP SISWA PADA PELAJARAN AKUNTANSI TERHADAP PRESTASI BELAJAR AKUNTANSI DI SMA NEGERI 1 BAGANSINEMBAH - Nurmas Dalema; Sri Kartikowati; Rina Selva Johan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The study aims to determine the effect of student perceptions and attitudesof students on accounting learning achievment. The population is students of class XI IPS SMA Negeri 1 Bagansinembah as many as 166 students, and the sample of 106 students.Data collection using questionnaires and documentation techniques. Analysis of data used is multiple linear regression. The result of the research based on multiple linear regression showed students 'perceptions and students' attitudes have an effect on students learning achievment of class XI IPS 1. This can be seen from the value of constanta (a) of 7, 686 and the value of regression coefficient (b) of 1, 171, and 1, 378 with the regression equation 7,686 + 1,371 +, 378. Judging from the calculation of R2 (R Square) obtained value of 0.273. This means that the contribution of students' perceptions and attitudes to accounting lessons on accounting learning achievement in SMA Negeri 1 Bagansinembah is 27.3%.Key Words: Perception, Attitude, Learning Achievement